2012
DOI: 10.2478/v10172-012-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics Analysis of Non-Metallic Inclusions Formation in the Liquid Steel Flow Through Continuous Casting Tundish

Abstract: Experiments were conducted at industrial plant to determine the free and total oxygen contents in molten steel in the tundish during continuous casting blooms of sizes 280×280 mm. On the basis of industrial experiment results a thermodynamic evaluation of non metallic inclusion formation in liquid steel was performed. Software FactSage R with thermodynamic base packages were tested and applied to calculate equilibrium formation of oxides and sulphides. The results showed the effect of oxygen contents and tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…The obtained pattern of NMI behavior indicates a possibility of liquid steel refining, also during continuous casting, especially when using refining powder and impact pad in the tundish. The recorded quantity of NMIs in liquid steel samples for tundish variants during introducing the alloy addition was similar to the results obtained in the casting sequences, during which no interference in the tundish powder was made . It is therefore concluded that the skilled introduction of the alloy addition to liquid steel via tundish powder will not have any adverse effect of increasing the NMI contents of the steel being cast.…”
Section: Resultssupporting
confidence: 80%
“…The obtained pattern of NMI behavior indicates a possibility of liquid steel refining, also during continuous casting, especially when using refining powder and impact pad in the tundish. The recorded quantity of NMIs in liquid steel samples for tundish variants during introducing the alloy addition was similar to the results obtained in the casting sequences, during which no interference in the tundish powder was made . It is therefore concluded that the skilled introduction of the alloy addition to liquid steel via tundish powder will not have any adverse effect of increasing the NMI contents of the steel being cast.…”
Section: Resultssupporting
confidence: 80%
“…It is only possible to limit supercritical and dimensionally critical NMIs occurring in steel, which adversely affect CSC and plastic working processes and, as a consequence, the functional properties of the finished products. This explains the special interest in NMIs and research undertaken in many research centers on the possibility of removing NMIs during steel production …”
Section: Introductionmentioning
confidence: 99%
“…This explains the special interest in NMIs and research undertaken in many research centers on the possibility of removing NMIs during steel production. [1][2][3][4] Modeling studies, both physical and numerical (Computational Fluid Dynamics-CFD) are research methods that are commonly used for the investigation of the problems of removing NMIs from liquid steel. Both methods support and complement each other; therefore, they are often combined in a single research program.…”
Section: Introductionmentioning
confidence: 99%
“…FactSage, a software program relying on the Gibbs free energy minimization method, was employed for calculations. The general form of the equation for the system's components (elements, stoichiometric compounds) takes on the form of the following expression [18]:…”
Section: Methodsmentioning
confidence: 99%